Inter-annual variations in the hydrochemistry of Alappuzha mud banks, southwest coast of India. (1st April 2019) - Mathew, Dayana; Gireeshkumar, T.R.; Udayakrishnan, P.B.; Muraleedharan, K.R.; Madhu, N.V.; Nair, M.; C.Revichandran,; Balachandran, K.K.
Abstract: The changes in the hydro-chemical properties of a near shore waters of Alappuzha, southwest coast of India, where the mud banks and coastal upwelling are co-existent, are presented based on two time-series measurements taken during 2014 and 2016. The meteorological data show that the wind speed was significantly high during 2014 as compared to that during 2016 ( p  < 0.01). As a result, the shoreward propagation and persistence of hypoxic upwelling waters were more prominent in the mud banks during 2014, even though the coastal upwelling was generally more intense during 2016. This indicates that irrespective of the intensity of upwelling, the incursion of hypoxic waters towards the shallow coastal environment is dependent on the local meteorological conditions such as winds. The coastal upwelling generally increased the concentrations of nutrients and chlorophyll a but marked increase in the nitrate levels during 2014 favoring a massive diatom bloom ( Fragelaria oceanica ) is noteworthy, as it is an indicator of the abundance of Indian oil sardines ( Sardinella longiceps ), the popular mud bank fishery. Highlights: The study elaborates the chemical hydrography of mud banks and its inter-annual variations (2014 and 2016). Upwelling induced near shore hypoxia persists both the years and was more intense during 2014. Shoreward propagation of hypoxic waters depends on the intensity of winds. Upwelling induced nutrient enrichment and subsequent increase in Chlorophyll a was noticed.